CD36 inhibition enhances the anti-proliferative effects of PI3K inhibitors in PTEN-loss anti-HER2 resistant breast cancer cells - You-Yu Liu; Wei-Lun Huang; Sin-Tian Wang; Hui-Ping Hsu; Tzu-Ching Kao; Wei-Pang Chung; Kung-Chia Young (Cancer & Metabolism)
Abstract Background HER2-positive patients comprise approximately 20% of breast cancer cases, with HER2-targeted therapy significantly improving progression-free and overall survival. However, subsequent reprogramed tumor progression due to PI3K signaling pathway activation by PIK3CA mutations and/or PTEN-loss cause anti-HER2 resistance. Previously, alpha isoform-specific PI3K inhibitors were shown to potentiate HER2-targeted therapy in breast cancer cells carrying PI3K pathway alterations with less potent effects on PTEN-loss than PIK3CA-mutant cells. Therefore, seeking for alternative combination therapy needs urgent attentions in PTEN-loss anti-HER2 resistant breast cancer. Methods Since remodeling of fatty acid (FA) metabolism might contribute to HER-positive breast cancer and is triggered by the PI3K signal pathway, herein, we examined the effects of the inhibition of endogenous FA conversion, SCD-1 or exogenous FA transport, CD36, in combination with PI3K inhibitors (alpelisib and inavolisib) in anti-HER2 resistant PTEN-loss breast cancer cells. Results The activated HER2/PI3K/AKT/mTOR signaling pathway positively correlated with SCD-1 and CD36 expression in PTEN-loss breast cancer cells. PI3K inhibition downregulated SCD-1, and accordingly, the addition of the SCD-1 inhibitor did not augment the antiproliferative effects of the PI3K inhibitors. CD36 was upregulated by blocking the PI3K signal pathway or limited serum supplementation, indicating that suppressing CD36 may decrease the excess transport of exogenous FA. The addition of the CD36 inhibitor synergistically enhanced the anti-proliferative effects of the PI3K inhibitors. Conclusion Simultaneously targeting the PI3K signaling pathway and exogenous FA uptake could potentially be advantageous for patients with PTEN-loss anti-HER2 resistant breast cancer.